Membranous nephropathy associated with profound hypothyroidism - Singhania, Girish (Clin Case Rep, 2019)
Membranous nephropathy can be primary or secondary. Although common causes of secondary MN are malignancy and lupus, hypothyroidism was rarely reported. Providers should check thyroid function tests in patients with unexplained nephrotic proteinuria.